Electrospun polyimide ultrafine non-woven fabrics with high whiteness and good thermal stability from organo-soluble semi-alicyclic polyimides: Preparation and properties - C. Y. Guo; Q. W. Wang; J. G. Liu; L. Qi; M. G. Huangfu; X. Wu; Y. Zhang; X. M. Zhang (eXPRESS Polymer Letters)
A series of organo-soluble polyimide (PI) resins were synthesized by a two-step chemical imidization reaction from two semi-alicyclic dianhydrides, 1,4-dihydroxyphenyl-dicyclohexanecarboxylate-3,3′,4,4′-tetracarboxylic acid dianhydride (HTA-HQ, I) and 4,4′-dihydroxybiphenyl dicyclohexanecarboxylate-3,3′,4,4′-tetracarboxylic acid dianhydride (HTABP, II) and two rigid-rod aromatic diamines, 2,2′-dimethylbenzidine (DMBZ, a) and 2,2′-bis(trifluoromethyl)benzidine (TFMB, b), respectively. Then, PI ultrafine non-woven fabrics were successfully fabricated via a one-step electrospinning procedure with the synthesized semi-alicyclic PI resins dissolved in N,N-dimethylacetamide (DMAc), followed by heat treatment at 200 °C. Comparatively, the standard wholly aromatic PI fabric, poly(pyromellitic dianhydride-oxydianiline) (PI-ref, PMDA/ODA) was prepared by a two-step electrospinning procedure with poly(amic acid) (PAA), followed by the high-temperature imidization procedure up to 350 °C. The derived electrospun semi-alicyclic PI non-woven fabrics exhibited much higher optical reflectance and whiteness than that of the PI-ref. For example, PI-IIb (HTA-BP/TFMB) fabric showed an optical reflectance (R457) value of 90.6% at the wavelength of 457 nm and whiteness index (WI) of 92.7, which were quite higher than those of PI-ref (R457: 37.3%; WI: 59.0). In addition, the semi-alicyclic PI fabrics exhibited good thermal stability with the glass transition temperatures (Tg) higher than 217°C.